Contribution to the Petrographic Study of the Geological Formations of the Mbanga Sector and its Headwaters in the Tshela Territory (Central Kongo, DRC) - Djonive Munene; Raphael Matamba Jibikila; Joël Lohad Etshekodi; Ravely Lusakueno Nsieto; Hugues Kasongo Kanyinda; Emmanuel Kalemba Ngungi; Audrey Katakanga N’kembo; Raphael Palata Kadjeng; Vanshok Ekoko Bolua Mpenge; Gertrude Mbumbu Luswamu (Analecta)
In order to fill the glaring gaps in the geological data for the Mbanga region and surrounding area, in the Province of Kongo-Central in DR Congo, geological investigations were carried out in the field over a three-week period. The results obtained, coupled with those from the laboratory, led to the identification of eight different lithofacies in the study area, namely: metaryolites, sericite schists and biotitose schists, all with grey to greenish grey facies. This work consists of a detailed petrographic study to identify the different facies of the West Congo Supergroup belonging to the Mayumbian Group and the Zadinian Group. The geology of the Mbanga sector and its surroundings is made up of metamorphic layers of volcanic and sedimentary origin. The various rock formations in our study area are grouped into two West Congo Supergroup groups; the metarhyolite formation belongs to the Tshela/Seke-Banza Group (Mayumbian) and the others belong to the Matadi Group (Zadinian).